RANCANG BANGUN PENYIRAM TANAMAN OTOMATIS MENGGUNAKAN SESOR KELEMBABAN TANAH BERBASIS ARDUINO - Armanto Armanto (LPPM UNIVERSITAS BINA INSAN, 2019)
Food self-sufficiency is a government program that is currently being actively promoted, so that Indonesia can be independent in providing food by the end of 2019. Indonesia besides being a maritime country is also an agricultural country with fertile land with 2 seasons, namely the rainy season and the dry season. In the rainy season food plants usually do not need to be watered because they have enough rain water. Whereas in the dry season the plants must be watered regularly in accordance with soil moisture conditions. Farmers usually do not grow food in the dry season for fear that it will not grow well and crop failure. Dependence of farmers with the season causes farmer production to decline and becomes an obstacle in the success of the food self-sufficiency program. To overcome the constraints of the dry season and so that farmers can still plant crops in the dry season, we need an information and communication technology-based agricultural tool product in the form of a programmed chip mircrocontroller so that it can control watering plants automatically based on soil moisture that is detected using domestic soil moisture sensors . This tool will detect whether the soil where the planting is dry so that the tool can control watering automatically when the soil lacks the element of water. So farmers do not need to do watering manually. So that plants can continue to flourish even though it is the dry season. In addition to helping farmers this tool can also be installed on plantations, seedbed nurseries, urban parks, hotels, offices, and in homes that have parks or plants that need regular watering. Keywords— Soil Moisture Sensor, Microcontroller, Arduino